IDENTIFICATION OF -308 TNF-α PROMOTER SINGLE NUCLEOTIDE POLYMORPHISM IN ACTIVE AND PASSIVE SMOKERS - Gracia A.V. Pollo; Rooije R.H. Rumende; Trina E. Tallei (JURNAL ILMIAH SAINS, 2019)
IDENTIFICATION OF -308 TNF-α PROMOTER SINGLE NUCLEOTIDE POLYMORPHISM IN ACTIVE AND PASSIVE SMOKERS ABSTRACTTumour necrosis factor-α (TNF-α) is one of the pro-inflammatory cytokines that play a role in the inflammatory process, immune system development, and apoptosis. This protein is encoded by the TNF-α gene. Several studies had linked the presence of polymorphisms in the TNF-α promoter region with susceptibility to the onset of chronic obstructive pulmonary disease (COPD) in active and passive smokers. This study aimed to identify and analyze the nucleotide polymorphism in TNF-α gene promoter regions in active and passive smokers in Manado. The method used in this study included blood sampling, DNA extraction, amplification of -308 TNF-α promoter region, sequencing and data analysis. The softwares used for data analysis were Geneious, Multalin, Clustal Omega and DnaSP. DnaSP was used to compute the level of polymorphism based on haplotype statistics. The results did not show single nucleotide polymorphism at position -308 in TNF-α gene promoters in active and passive smokers. This was because at that position, the nucleotides were both in the form of guanosine monophosphate and there were no mutation caused by cigarette smoke exposure.Keywords: active smoker, passive smoker, single nucleotide polymorphism, TNF-α promoter DETEKSI POLIMORFISME NUKLEOTIDA TUNGGAL-308 PROMOTERTNF-α PADA PEROKOK AKTIF DAN PASIF ABSTRAKTumor necrosis factor-α (TNF-α) merupakan salah satu sitokin pro-inflamasi yang berperan dalam proses inflamasi, perkembangan sistem imun, dan apoptosis. Protein ini dikode oleh gen TNF-α. Beberapa penelitian telah mengkaitkan adanya polimorfisme pada daerah promoter TNF-α dengan kerentanan terhadap timbulnya chronic obstructive pulmonary disease (COPD) pada perokok aktif maupun pasif. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis polimorfisme nukleotida tunggal pada posisi -308 dari promoter gen TNF-α perokok aktif dan pasif. Metode yang digunakan dalam penelitian ini meliputi pengambilan sampel darah, ekstraksi DNA, amplifikasi daerah -308 promoter gen TNF-α, sekuensing serta analisis data. Analisis data menggunakan perangkat lunak Geneious, BLAST, Multalin, Clustal Omega dan DnaSP. Perangkat DnaSP akan mengkomputasi tingkat polimorfisme berdasarkan statistik haplotype-based. Hasil yang didapatkan menunjukkan bahwa polimorfisme nukleotida tunggal pada posisi -308 dari promoter gen TNF-α antara perokok aktif dan pasif tidak ditemukan. Hal ini dikarenakan oleh pada posisi tersebut, nukleotidanya sama-sama berbentuk guanosin monofosfat dan tidak terjadi mutasi akibat pengaruh paparan asap rokok.Kata kunci: perokok aktif, perokok pasif, single nucleotide polymorphism, TNF-α promoter